2016
DOI: 10.18632/oncotarget.9962
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase enhances resistance to 5-fluorouracil in colorectal cancer cells through inhibition of the ASK1-p38 MAPK pathway

Abstract: Nicotinamide N-methyltransferase (NNMT), which converts nicotinamide to 1-methylnicotinamide (1-MNA), is overexpressed in a variety of human cancers and serves as a potential anti-cancer target. In this study, we investigated the effect of NNMT on 5-fluorouracil (5-FU) sensitivity of colorectal cancer (CRC) cells, and the underlying mechanisms. Our results show that down-regulation of NNMT in CRC HT-29 cells diminishes 5-FU resistance, while over expression of NNMT in SW480 cells enhances it. NNMT reduces reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 20 publications
4
75
0
Order By: Relevance
“…A previous study demonstrated that the phosphoinositide 3-kinase/protein kinase B signaling pathway exerts a critical function in the NNMT-mediated invasion of renal carcinoma cells (34). It has been revealed that NNMT increased the resistance to 5-fluorouracil partially through suppressing the signal-regulating kinase 1/p38 mitogen-activated protein kinase signaling pathway in colorectal cancer cells (17). Therefore, additional signaling pathways may be involved in the NNMT-mediated migration and invasion of gastric cancer cells and further studies are required to confirm these conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that the phosphoinositide 3-kinase/protein kinase B signaling pathway exerts a critical function in the NNMT-mediated invasion of renal carcinoma cells (34). It has been revealed that NNMT increased the resistance to 5-fluorouracil partially through suppressing the signal-regulating kinase 1/p38 mitogen-activated protein kinase signaling pathway in colorectal cancer cells (17). Therefore, additional signaling pathways may be involved in the NNMT-mediated migration and invasion of gastric cancer cells and further studies are required to confirm these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the serum levels of NNMT were significantly increased in patients with colorectal, lung and renal cell carcinoma compared with those in the control group (10,14,15). Previous studies have also demonstrated that the upregulation of NNMT is associated with poor prognosis, advanced tumor stage, tumor cell migration and invasion (9,16,17). Although, overexpression of NNMT has been identified in gastric cancer (18), the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…NNMT mediates SAM depletion and attenuating histone methylation in various cells, including cancer cells, which resulted in the extensive gene expression changes in the tumor stroma. Besides, NNMT can promote the CRC cell growth and increase the resistance of CRC cells to 5‐fluorouracil through the 1‐MNA production . High expression of NNMT has been reported in multiple cancer types .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, NNMT can promote the CRC cell growth and increase the resistance of CRC cells to 5-fluorouracil through the 1-MNA production. 5,6 High expression of NNMT has been reported in multiple cancer types. [7][8][9][10][11][12] Several studies have shown that the elevated NNMT level in cancer can be used for the early diagnosis and noninvasive diagnosis of some malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgical resection has been the primary treatment modality, chemotherapy is still the important treatment for CRC 1. The chemotherapeutant, 5-fluorouracil (5-FU), causes cytotoxic damage by way of targeting the metabolism of RNA bases.…”
Section: Introductionmentioning
confidence: 99%